MULTI-OBJECTIVE OPTIMIZATION OF THE MAIN DESIGN PARAMETERS OF THE HYDRAULIC CRANE-MANIPULATOR INSTALLATIONS OF MOBILE MACHINES - I. A. Lagerev; A. V. Lagerev (Вестник СибАДИ, 2017)
Presents a methodology for optimal design of crane-manipulator installations of mobile transport technological machines at the pre-design stage of development of the technical proposal. Predesign optimization allows to comprehensively determine the optimum combination of a sufficiently large number of basic design parameters – the characteristic dimensions of metal structures of installation (lengths and dimensions of cross sections, links, and mounting dimensions for hydraulic cylinders) and characteristics of the hydraulic system (working pressure and flow rate of the working fluid).